Nilai-Nilai Buddhayāna dalam Membentuk Budaya Organisasi yang Berkelanjutan - Panya Lita Teri, Intan; Satyawati, Wulan; Ardianto, Hendri; Nagatirtha, Partama; Meyliana, Henny (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
This research aims to explore how organizations can implement these Buddhayāna values into their organizational culture. The research utilizes a systematic literature review method to synthesize relevant research findings. The results indicate that Buddhayāna values, such as non-sectarianism, pluralism, inclusivism, and belief in Dharma, play a significant role in shaping sustainable organizational culture. Organizational culture inspired by Buddhayāna values is reflected in the examples and practices of figures like Bhiksu Ashin Jinarakkhita. Through understanding and implementing these values, organizational culture can serve as a means for individual growth and collective progress, as well as inspire positive transformation.